Exploring new belousovite‐related zinc and cadmium alkali sulfate halides: synthesis and structural variability. Issue 3 (26th May 2022) - Borisov, Artem S.; Siidra, Oleg I.; Charkin, Dmitri O.; Zagidullin, Karim A.; Burshtynovich, Ruslan K.; Vlasenko, Natalia S.
Abstract : Fourteen new belousovite‐related compounds have been prepared via melt and evaporation techniques. They adopt the layered structure and constitute a morphotropic series. The apophyllite‐type layers in these structures undergo different corrugations, increasing sharply for CsZn(SO4 )I. Abstract : Fourteen new belousovite‐related compounds, A Zn( T O4 ) X ( A = K, Rb, Cs, Tl, NH4 ; T = S, Se; X = Cl, Br, I) have been prepared via melt and evaporation techniques by reacting AX and Zn T O4 either at high temperatures or in hot aqueous solutions. They adopt the layered structure of the belousovite archetype, and constitute a morphotropic series. The apophyllite‐type layers in these structures undergo different corrugations, most pronounced in the case of CsZn(SO4 )I. In addition, during the study two species unrelated to belousovite, namely Na4 Zn(SO4 )2 Cl2 and Cs2 Cd3 (SO4 )4, were found with framework crystal structures having different topology and belonging to new structure types.